Theracurmin inhibits intestinal polyp development in Apc‐mutant mice by inhibiting inflammation‐related factors. Issue 4 (22nd February 2020) - Adachi, Saeko; Hamoya, Takahiro; Fujii, Gen; Narita, Takumi; Komiya, Masami; Miyamoto, Shingo; Kurokawa, Yurie; Takahashi, Maiko; Takayama, Tetsuji; Ishikawa, Hideki; Tashiro, Kosuke; Mutoh, Michihiro
Abstract: Colorectal cancer (CRC) is the second leading cause of cancer death worldwide. Therefore, it is important to establish useful methods for preventing CRC. One prevention strategy involves the use of cancer chemopreventive agents, including functional foods. We focused on the well‐known cancer chemopreventive agent curcumin, which is derived from turmeric. However, curcumin has the disadvantage of being poorly soluble in water due to its high hydrophobicity. To overcome this problem, the formation of submicron particles with surface controlled technology has been applied to curcumin to give it remarkably improved water solubility, and this derived compound is named Theracurmin. To date, the preventive effects of Theracurmin on hereditary intestinal carcinogenesis have not been elucidated. Thus, we used Apc ‐mutant mice, a model of familial adenomatous polyposis, to evaluate the effects of Theracurmin. First, we showed that treatment with 10‐20 µM Theracurmin for 24 hours reduced nuclear factor‐κB (NF‐κB) transcriptional activity in human colon cancer DLD‐1 and HCT116 cells. However, treatment with curcumin mixed in water did not change the NF‐κB promoter transcriptional activity. As NF‐κB is a regulator of inflammation‐related factors, we next investigated the downstream targets of NF‐κB: monocyte chemoattractant protein‐1 (MCP‐1) and interleukin (IL)‐6. We found that treatment with 500 ppm Theracurmin for 8 weeks inhibited intestinal polyp development and suppressed MCP‐1 and IL‐6 mRNA expression levels in the parts of the intestine with polyps. This report provides a proof of concept for the ongoing Theracurmin human trial (J‐CAP‐C study). Abstract : Min mice were fed a basal diet (open box), a diet containing 500 ppm Theracurmin (gray‐filled box), and a diet containing 500 ppm curcumin (black‐filled box) for 8 weeks.